ANALISIS PENGARUH JOB SATISFACTION, WORKPLACE SPIRITUALITY DAN EFFECTIVE LEADERSHIP PADA ORGANIZATIONAL CITIZENSHIP BEHAVIOR KARYAWAN RSUD KOTA KISARAN - Siagian, Dicki Alfajani; Puspa, Tiara (Peneliti.net, 2024)
The role of humans in company organizations cannot be ignored, even though they already have quite sophisticated technology and infrastructure. Therefore, human performance in the organization must be optimal so that performance in the organization is good, so Organizational Citizenship Behavior is needed. Knowledge about Organizational Citizenship Behavior is something interesting to study in relation to Job Satisfaction, Workplace Spirituality & Effective Leadership so this research will attempt to examine the influence of Job Satisfaction, Workplace Spirituality & Effective Leadership on Organizational Citizenship Behavior. The sample was taken randomly and as many as 87 Kisaran City Regional Hospital employees participated as respondents. Data analysis uses multiple linear regression and produces that Organizational Citizenship Behavior can be positively influenced by Job Satisfaction, Workplace Spirituality & Effective Leadership. Good Job Satisfaction and support from leaders and welfare in the work environment really encourage the achievement of Organizational Citizenship Behavior of employees in carrying out work at the Kisaran City Regional Hospital.